Color Edge Detection Based On The Fusion Of Hue Component And Principal Component Analysis (International Journal of Engineering and Computer Science, 2017)
This paper evaluates the performance of HUE, PCA and fusion of HUE and PCA based colour edge detection techniques. Edge detection has found to be most significant part of many critical vision applications. It really results in the black and white (binary) image where each object is differentiate by lines (either black or white). Edges are basically the location in the image where sharp changes exist. It's been discovered that the all of the existing techniques has neglected the utilization of colours while detecting the edges however in many applications an area could be categorized in relation to the colour. This paper indicates that a majority of the existing techniques fail in the event of images with complex background.